Insurance in cooperation with the Agrarian Fund and the State Food and Grain Corporation of Ukraine - Кравчук, Олена Василівна (Technology audit and production reserves, 2015)
The article analyzes the insurance of agricultural products in cooperation with the Agrarian Fund and the State Food and Grain Corporation of Ukraine. Domestic agricultural enterprises have advanced the production of cereals and occupy leading positions in global markets, but despite good results, producers do not always work in favorable conditions and have several problems. First of all, we know that the results of economic activity of the agricultural sector most dependent on weather conditions. Also, a major problem is the availability of working capital in certain periods, because feature of agricultural production is seasonal and there are very important dates. Find the necessary working capital in the set time is extremely important for the activity of farmers, so cooperation with the Agrarian Fund and the State Food and Grain Corporation of Ukraine is a priority, especially in the absence of reliable and stable system of credit. The mechanism of interaction between farms with these government agencies and outlines the role of insurance in it. The terms of insurance contracts and revealed their impact on farmers.